Comparison of Cortical Autonomic Network-Linked Sympathetic Excitation by Mueller Maneuvers and Breath-Holds in Subjects With and Without Obstructive Sleep Apnea - Taylor, Keri S.; Keir, Daniel A.; Haruki, Nobuhiko; Kimmerly, Derek S.; Millar, Philip J.; Murai, Hisayoshi; Floras, John S. (Frontiers in Physiology, 2021)
In healthy young volunteers, acquisition of bold oxygen level-dependent (BOLD) magnetic resonance (MR) and muscle sympathetic nerve (MSNA) signals during simulation of obstructive or central sleep apnea identified cortical cardiovascular autonomic regions in which the BOLD signal changed synchronously with acute noradrenergic excitation. In the present work, we tested the hypothesis that such Mueller manoeuvres (MM) and breath-holds (BH) would elicit greater concomitant changes in mean efferent nerve firing and BOLD signal intensity in patients with moderate to severe obstructive sleep apnea (OSA) relative to age and sex matched individuals with no or only mild OSA (Apnea Hypopnea Index, AHI, <15 events/hour). Forty-six participants, 24 with OSA (59±8 years; AHI 31±18 events/h [mean±SD]; 7 women) and 22 without (58±11 years; AHI 7±4; 9 women) performed a series of 3 MM and 3 BH, in randomly assigned order, twice: during continuous recording of MSNA from the right fibular nerve and, on a separate day, during T2*-weighted echo planar functional MR imaging. MSNA at rest was greater in those with OSA (65±19 vs 48±17 bursts per 100 heart beats; p<0.01). MM and BH elicited similar heart rate, blood pressure, and MSNA responses in the 2 cohorts; group mean BOLD data were concordant, detecting no between-group differences in cortical autonomic region signal activities. The present findings do not support the concept that recurring episodes of cyclical apnea during sleep alter cortical or peripheral neural responsiveness to their simulation during wakefulness by volitional Mueller manoeuvres or breath-holds.